IMPLEMENTASI STRATEGI PENGUATAN FUNGSI PENGAWASAN DI INSPEKTORAT KOTA METRO - Arie Wibowo (LPPM Universitas Abdurrab, 2026)
Based on the research findings, it can be concluded that the implementation of strategies to strengthen the supervisory function plays a strategic role in improving the effectiveness of oversight performance at the Metro City Inspectorate. The implementation of strategies grounded in integrity, professionalism, discipline, collaboration, and digital adaptation has been proven to influence the quality of audit processes, the timeliness of audit report preparation, and the effectiveness of follow-up on recommendations. Nevertheless, the optimization of the supervisory function still faces structural constraints, including a limited number of supervisory human resources, unequal distribution of functional competencies among auditors, and an increasing workload arising from both regular and mandatory assignments from external institutions. These conditions cause supervision to be not fully risk-based and to remain largely administrative in nature.As a strategic measure, the optimization of supervision should be directed toward the implementation of Risk-Based Auditing (RBA) by focusing available resources on areas and programs with the highest levels of risk. This approach enables the Inspectorate to maintain the quality of supervision despite human resource limitations. Where possible, this strategy should be supported by proposals for additional functional auditor positions based on a realistic needs analysis of the Metro City Inspectorate. Furthermore, continuous competency development should be prioritized through intensive training in auditing, internal control, and investigation. Enhancing the technical capacity of functional auditors is expected to accelerate audit processes, improve analytical quality, and generate more substantive and corrective recommendations.In addition, workload balancing should be undertaken through mapping the distribution of tasks among functional auditors. The redistribution of assignments, adjustment of audit quota standards, and alignment of tasks with individual competencies will improve efficiency and maintain supervisory quality without relying solely on short-term staff increases. This approach represents a realistic solution to the growing complexity of supervisory demands.